MEMAHAMI & MEMAKNAI KONSEP-KONSEP LEX AETERNA SEBAGAI TEOLOGI HUKUM MENURUT AGUSTINUS, ALBERTUS MAGNUS, & THOMAS AQUINAS - Siti Nur Azizah; Wagiman; Adrian Bima Putra; Brian Matthew (LPPM Universitas Ekasakti, 2024)
The article will explore the concept of ‘Lex Aeterna’ from Augustine, Albertus Magnus, to Thomas Aquinas. Lex Aeterna scholars can refer to Aquinas through the Summa Theologica which is essentially an idea of ??an absolute, eternal, and wise order in the Universe created and established by God Himself. Everything that exists and moves directs everything to its proper purpose in God and through Divine reason has the nature of law. Although Divine reason is not subject to time, but is eternal. The law by which God governs the Universe must also be eternal. Therefore, every Divine concept is true because of its own reason. This law is the final authority that humans must turn to so that they can know without a doubt what they should do and what they should avoid. Some people know about lex aeterna because God has implanted in the human soul the principles of proper action. This is human participation in lex aeterna, a participation called natural law. Based on this, humans have knowledge of general principles and certain teachings about rights and justice. No one can know the lex aeterna as it is and in its entirety. Every rational being knows it in its reflection or effect. All law, partaking of reason, originates or originates from the eternal law. For nothing is just and legitimate except that which has been derived from the lex aeterna. Lex Aeterna itself is ultimately understood as the theology of law, namely the universe itself, namely reality which is composed and regulated by a natural order or cosmic law.